An abasic site analogue activates a c-Ha-ras gene by a point mutation at modified and adjacent positions. - Kamiya, H (1992)
Synthetic c-Ha-ras genes with an analogue of an abasic site in the first or the second position of codon 12, or in the second position of codon 61 were constructed and transfected into NIH3T3 cells. The genes with the lesions in codon 12 exhibited more focus formation than a normal c-Ha-ras gene, while the gene with the lesion in codon 61 did not. Transformed cells were isolated from the foci, and the c-Ha-ras genes present in the transformants were analysed. A point mutation to A in the modified position was found most frequently in the cases of ras genes modified in codon 12. Surprisingly, point mutations in the adjacent position were also detected. These results indicate that dTMP, and not dAMP, was mainly incorporated into the sites opposite to the abasic site analogue, and that incorrect deoxynucleotides were incorporated in the position adjacent to the abasic site analogue.